Local and systemic neutrophilic inflammation in patients with lung cancer and chronic obstructive pulmonary disease - Vaguliene, Neringa (BioMed Central, 2013)
BACKGROUND: Recent investigations suggest that neutrophils play an important role in the immune response to lung cancer as well as chronic obstructive pulmonary disease (COPD). The aim of this study was to evaluate the amount of neutrophils and markers of their activity in lung cancer and COPD and in coexistence of these two diseases. METHODS: In total, 267 persons were included in the study: 139 patients with lung cancer, 55 patients with lung cancer and COPD, 40 patients with COPD, and 33 healthy subjects. Peripheral blood and BAL fluid samples were obtained for cell count analysis and determination of NE, MPO levels and ROS production. NE and MPO levels in the serum and BAL fluid were determined by ELISA. ROS production was analyzed by flow cytometer. RESULTS: The percentage, cell count of neutrophils and neutrophil to lymphocyte ratio in the peripheral blood were significantly higher in lung cancer patients with or without COPD compared to COPD patients or healthy individuals (P < 0.05). The percentage and cell count of neutrophils in BAL fluid were significantly lower in patients with lung cancer with or without COPD than in patients with COPD (P < 0.05). However, BAL fluid and serum levels of both NE and MPO were significantly higher in patients with lung cancer than COPD patients or healthy individuals (P < 0.05). Neutrophils produced higher amounts of ROS in patients with lung cancer with or without COPD compared with COPD patients or healthy individuals (P < 0.05). CONCLUSIONS: The results from this study demonstrate higher degree of local and systemic neutrophilic inflammation in patients with lung cancer (with or without COPD) than in patients with COPD.